Temporal Regulation of Peripheral BDNF Levels during Cocaine and Morphine Withdrawal: Comparison with a Natural Reward - Geoffroy, Hélène Anne-Sophie (Int J Neuropsychopharmacol, 2015)
BACKGROUND: Brain-derived neurotrophic factor (BDNF) is a neurotrophin that has long been studied in the field of addiction and its importance in regulating drug addiction–related behavior has been widely demonstrated. The aim of our study was to analyze the consequences of a repeated exposure to drugs of abuse or natural reward on plasma BDNF levels during withdrawal. METHODS: Rats were chronically injected with morphine (subcutaneously, 5mg/kg) or cocaine (intraperitoneally, 20mg/kg) or fed with a butter biscuit (per os, 4g) once per day for 14 days. Blood collection was performed on the 1st (withdrawal day 1 or WD1) or on (WD14), either at the same time point rats had been exposed to drugs or natural reward or at a different time point (used to quantify basal brain-derived neurotrophic factor levels). RESULTS: Cocaine treatment led to a rapid (WD1) and persistent (WD14) decrease of basal BDNF levels compared with saline-treated animals, whereas morphine induced an increase on WD14 without any alteration on WD1. On the contrary, the natural reward induced a significant increase of basal brain-derived neurotrophic factor levels only on WD1. The analysis of BDNF levels at the usual time point at which animals had been exposed showed that both drugs, but not the natural reward, increased BDNF levels compared with basal levels. CONCLUSION: Our data highlight that only drugs of abuse are able to persistently alter BDNF levels and to induce specific variations of this neurotrophic factor at the usual hour of injection.